1989
DOI: 10.1038/337279a0
|View full text |Cite
|
Sign up to set email alerts
|

Role of transcriptional interference in the Drosophila melanogaster Adh promoter switch

Abstract: The Drosophilia melanogaster alcohol dehydrogenase (Adh) gene is transcribed from two closely linked promoters, which are regulated by two upstream enhancers. The proximal promoter is active primarily in first to early third-instar larvae, whereas the distal promoter is active in late third-instar larvae and adults. The Adh larval enhancer and the proximal promoter are separated by the Adh adult enhancer and the distal promoter. Because the proximal promoter is turned off just as the distal promoter is turned … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

7
111
1

Year Published

1990
1990
2001
2001

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 142 publications
(121 citation statements)
references
References 23 publications
7
111
1
Order By: Relevance
“…The proximal promoter is active in first-to early third-instar larvae. The distal promoter then turns on and represses the proximal promoter by transcribing through it (Corbin and Maniatis 1989).…”
Section: Terminator-promoter Interactions On Genes Transcribed By Rnamentioning
confidence: 99%
“…The proximal promoter is active in first-to early third-instar larvae. The distal promoter then turns on and represses the proximal promoter by transcribing through it (Corbin and Maniatis 1989).…”
Section: Terminator-promoter Interactions On Genes Transcribed By Rnamentioning
confidence: 99%
“…6). The two transcripts are initiated from separate promoters, each having its own enhancer sequence (7). Transcripts from a proximal promoter are found predominantly in larvae, while transcripts from a distal promoter are found predominantly in adult flies (6).…”
mentioning
confidence: 99%
“…Transcripts from a proximal promoter are found predominantly in larvae, while transcripts from a distal promoter are found predominantly in adult flies (6). P-element-mediated transformation experiments have shown that all of the cis-acting sequence elements required for proper Adh expression are contained within a 8.6-kb SacI-ClaI genomic Adh fragment (7,8) and that a single replacement substitution can alter the catalytic efficiency of the alcohol dehydrogenase (ADH) enzyme (9). In addition, it has been demonstrated that nonreplacement sites must also play a role in determining the level of Adh expression (9, 10).…”
mentioning
confidence: 99%
“…At this time transcription switches to the distal transcript until the beginning of the pupa stage, although the level of transcription is much lower than it had been for the proximal transcript (Corbin & Maniatis, 1989). In adult flies the distal transcript is the major form.…”
Section: Introductionmentioning
confidence: 99%